Sacral Neuromodulation: Foray into Chronic Pelvic Pain in End Stage Endometriosis - Lavonius M; Suvitie P; Varpe P; Huhtinen H (HINDAWI LTD, 2022)
Copyright (C) 2017 Maija Lavonius et al. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.Excision of all endometriotic lesions is the method of choice in the treatment of severe endometriosis resistant to medical therapy. The infiltrating nature of the disease as well as extensive surgery may, however, cause chronic pain that cannot be relieved by either surgery or hormonal treatment. As a pilot treatment, we tested the effect of sacral neuromodulation (SNM) for four endometriosis patients suffering chronic pelvic pain and pelvic organ dysfunction after radical surgical treatment. Three out of four patients reported improvement in their symptoms during the neuromodulation testing period and a permanent pulse generator was installed. After 2.5 years, all three patients report better quality of life and want to continue with SNM.